Pengaruh Kompres Dingin dalam Penurunan Nyeri Pasien Post Percutaneous Coronary Intervention (PCI): Literature review - Andy Kristiyan; Hery Djagat Purnomo; Chandra Bagus Ropyanto (Holistic Nursing and Health Science, 2019)
Introduction: Complications in catheterization vascular access range from 1%-61%. One of interventions that can be taken to prevent hematoma and reduce pain in post PCI patients at off sheath is with cold compresses or ice bag. The fact shows that pain and hematoma in patient PCI in hospital just done by using sand bag therapy. There was a limited review about the use of ice bag to reduce pain in patients with PCI.Methods: Searched articles through Science Direct, PubMed, EBSCO and Google Scholar conducted using advanced searching with keywords including “ice bag”, “pain”, and “percutaneous coronary intervention”. Searching through Google Scholar using keywords involving “effectiveness of ice bag on pain in patient’s percutaneous coronary intervention (PCI)”.Results: There were three articles control trials and the results showed that implementation of cold compresses with ice bag for 20 minutes before and after catheter release in PCI measures was significant in reducing pain (P <0.05).Conclusion: Giving cold compresses can reduce pain because it can inhibit the fibber of small-diameter nerves in delivering pain stimuli.